2,2´-Dipyridyl diselenide: A chemoselective tool for cysteine deprotection and disulfide bond formation. - Ste.Marie, Emma J. (J Pept Sci, 2019)
There are many examples of bioactive, disulfide rich peptides and proteins whose biological activity relies heavily on proper disulfide connectivity. Regioselective disulfide bond formation is a strategy for the synthesis of these bioactive peptides, but many of these methods suffer from a lack of orthogonality between pairs of protected cysteine (Cys) residues, efficiency, and high yields. Here, we show the utilization of 2,2´-dipyridyl diselenide (PySeSePy) as a chemical tool for the removal of Cys-protecting groups and regioselective formation of disulfide bonds in peptides. We found that peptides containing either Cys(Mob) or Cys(Acm) groups treated with PySeSePy in TFA (with or without triisopropylsilane (TIS)) were converted to Cys-S–Se-Py adducts at 37 °C and various incubation times. This novel Cys-S–Se-Py adduct is able to be chemoselectively reduced by five-fold excess ascorbate at pH 4.5, a condition which should spare already installed peptide disulfide bonds from reduction. This chemoselective reduction by ascorbate will undoubtedly find utility in numerous biotechnological applications. We applied our new chemistry to the iodine-free synthesis of the human intestinal hormone guanylin, which contains two disulfide bonds. While we originally envisioned using ascorbate to chemoselectively reduce one of the formed Cys-S–Se-Py adducts to catalyze disulfide bond formation, we found that when pairs of Cys(Acm) residues were treated with PySeSePy in TFA, the second disulfide bond formed spontaneously. Spontaneous formation of the second disulfide is most likely driven by the formation of the thermodynamically favored diselenide (PySeSePy) from the two Cys-S–Se-Py adducts. Thus, we have developed a one-pot method for concomitant deprotection and disulfide bond formation of Cys(Acm) pairs in the presence of an existing disulfide bond.